UNStudio - Jeong, Ji-seong. (Seoul, Korea : CA Press Company Ltd, 2007)
UNStudio, the Dutch architectural design studio, is composed of highly skilled individuals from all over the world with backgrounds and technical training in numerous fields. Specialising in architecture, urban development and infrastructural projects, the wholly collaborative nature of the practice provides the basis for its long-term goals that are intended to define and guide the quality of the work. This book takes a look beneath the surface of the hugely successful practice and examines the workings of the integral approach and a non-hierarchical, complex, generative and integral design process that takes on board the numerous and varied aspects of a project including: time, use, circulation, construction, materials, systems, cost as well environmental and client needs. Emerging from this study is an architectural imagination where utility and philosophy combine to extend and deepen how we experience reality
Text in English and Korean.
Keywords: Architecture, Modern -- 20th century; Architectual firms -- Netherlands -- Amsterdam